Planejamento Educacional: olhares sobre o monitoramento e avaliação do Plano Municipal de Educação de Conchal/SP. - Silva, Débora Aparecida Martinho da (Universidade Federal de São Carlos, 2025)
The objective of this research was to analyze the debates and conflicts, in light of the bodies responsible for monitoring and evaluating the PME (Municipal Education Plan) of the city of Conchal/SP, regarding its implementation. The research was limited to the city of Conchal, a municipality belonging to the Mogi Mirim Education Board. The methodology, of a qualitative nature, consisted of a bibliographic survey, in addition to semi-structured interviews involving five actors, whose members were part of the Organizing Committee, the Technical Team, the Municipal Education Forum, the Municipal Education Commission, and one of these members represented the teachers of the Municipal Education Network. The specific objectives of this research were: a) to list the historical trajectory of the construction of national documents that structure the country's educational planning; b) to identify, through a state-of-knowledge research, themes related to the monitoring and evaluation of PMEs, considering the municipality of Conchal/SP of the Mogi Mirim/SP Education Board; c) to explain the processes of participation in the elaboration, monitoring and evaluation, through the expressions and understandings of the members involved in these processes; d) to analyze, based on the respondents' feedback, through a semi-structured survey, the involvement and impact of PME on education in the city of Conchal/SP. We hope that this research will provoke reflections regarding the quality of education in the country and, especially, in the city of Conchal/SP, taking into account the history of Brazilian educational planning. To this end, we chose to point out, through the data collected, the importance of civil society participation in the preparation, monitoring and evaluation of the PME, in order to obtain knowledge of their rights, while exercising their citizenship, seeking to raise awareness of the contribution to quality education at the municipal, state and national levels. The results showed that the monitoring and evaluation of the Conchal PME had flaws in its process, making it difficult to accurately measure the data for publicizing to civil society as a whole. The flaws presented were due to changes in government during the PME's term and the lack of awareness regarding the meaning and importance of the requirement recommended in the PNE (National Education Plan). Civil participation did not occur in a democratic and participatory manner, causing gaps in the democratic act. Compliance with the planning corroborates similar historical facts in Brazilian education, which were constantly changing due to government directions, not valuing a state policy, due to the political and personal interests of the rulers, in each period.
Educational Planning: views on the monitoring and evaluation of the Municipal Education Plan of Conchal/SP.
Keywords: Planejamento Educacional; Plano Municipal de Educação; Monitoramento e Avaliação; Conchal/SP; Educational Planning; Municipal Education Plan; Monitoring and Evaluation; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL